The effects of climate change in today’s world and some solutions to solve them (This article includes explanations of worldwide commits’ meetings and scientists research) - Askarova Mokhichekhra G`ulomovna (Peerian Journals Publishing, 2024)
NAIROBI, Oct 12 (Reuters) - The United Nations Climate Summit in Nairobi concluded today with an urgent call for immediate global action to combat climate change. Delegates from over 190 countries emphasized the need for enhanced international cooperation and commitment to reducing greenhouse gas emissions. And this meeting explored some effects of factories and their coming dengers. So, this article includes all about it and reveals some new prospects.
Keywords: World; climate change; summit; emissions